2019
DOI: 10.1016/j.ejmp.2019.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric modulated arc therapy with robust optimization for larynx cancer

Abstract: The aim of this study was to perform a comparison between robust optimization and planning target volume (PTV)-based optimization plans using volumetric modulated arc-therapy (VMAT) by evaluating perturbed doses induced by localization offsets for setup uncertainties in larynx cancer radiation therapy. Methods: Ten patients with early-stage (T1-2N0) glottis carcinoma were selected. The clinical target volume (CTV), carotid arteries, and spinal cord were contoured by a radiation oncologist. PTV-based and robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…However, that study was performed based on the PTV concept that has been quite controversial in both photon and proton radiotherapy [9,10]. As a solution based on CTV, robust optimization has been proven to protect normal tissue in various tumor sites [10][11][12][13][14]. In our study, the robust optimization technique was introduced for both the The same patient setup uncertainties were applied in robust optimization for both SRO and TRO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, that study was performed based on the PTV concept that has been quite controversial in both photon and proton radiotherapy [9,10]. As a solution based on CTV, robust optimization has been proven to protect normal tissue in various tumor sites [10][11][12][13][14]. In our study, the robust optimization technique was introduced for both the The same patient setup uncertainties were applied in robust optimization for both SRO and TRO.…”
Section: Discussionmentioning
confidence: 99%
“…The total scores are assigned 100 points, with the specific allocation is as follows: S T metrics [1][2][3][4] with total points of 24 are used to calculate the points of CTV dose coverage [V46.8Gy (%), V50 Gy (%)], conformity number (CN) and homogeneity index (HI). The rest 76 points are S O metrics [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] are assigned to specific dosevolume parameters of five OARs, where rectum, bowel, bladder, sigmoid and femoral heads shared 23, 22, 15, 9 and 7 points, respectively. The details of score points are shown in Table 2.…”
Section: Quick Plan Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce the errors caused by patients' respiratory movement in actual treatment, the Robust optimization technology was added to radiotherapy plan, and clinical studies had shown that it could not only improve the coverage rate of the clinical target area, but also reduce the dose of OARs.The Mahmoudzadeh team's experiment proved that the introduction of Robust optimization could potentially reduce the need for deep inspiration breath-hold technology, allowing patients to reduce the exposure dose to heart with breathe freely, and improve the dose coverage of tumor area 21 23 . This was slightly different from actual exposure dose of OARs dose parameters in this study, the exposure dose of ipsilateral lung V5 was higher than that without Robust optimization, because the improved CTV coverage in our study was at the expense of a low dose bath to healthy tissue, thereby delivering a higher volume of low dose to the ipsilateral lungs than that without Robust optimization plans.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] Moreover, the shorter delivery time of VMAT technique may result in better local disease control due to its biological advantages for cancer cell killing, the fewer delivered MUs could reduce the undesirable irradiation of healthy tissues and lower the probability of suffering from secondary cancer. [14][15][16][17][18][19] However, the approach of manual optimization parameter tuning and re-optimization is inefficient and very timeconsuming. So the prescriptive and data-driven technique has accumulated popularity in that can help automate the treatment planning process.…”
Section: Introductionmentioning
confidence: 99%